Can Urinary Nerve Growth Factor and Brain-Derived Neurotrophic Factor be used in the Diagnosis and Follow-Up of Voiding Dysfunction in Children? - Özdemir, Kadriye; Dinçel, Nida; Berdeli, Afig; Mir, Sevgi (Urology Journal, 2016)
Purpose: We investigated the utility of urinary nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) levels as non-invasive markers for diagnosis and evaluation of treatment efficacy in children with overactive bladder (OAB). Materials and Methods: This prospective study included 24 children with OAB and 30 healthy controls. At the time of diagnosis, micturition disorder symptom scores (MDSS) were determined, blood and urine samples were collected, and anticholinergic therapy was initiated. Clinical responses were evaluated, at the third and sixth month of treatment, by MDSS and urinary NGF, BDNF, and creatinine levels. Results: The patient group had significantly higher urine NGF/Cr ratio (975 ± 827 and 159 ± 84, respectively, P < .001) and BDNF/Cr ratio (5.98 ± 5.78 and 0.81 ± 0.70, respectively, P < .001) before treatment. Significantly decreased BDNF/Cr ratio was found at the sixth month (5.98 ± 5.78 and 2.24 ± 0.98, respectively, P = .004). NGF/Cr > 360 was found to have 87.5% sensitivity and 100% specificity, and BDNF/Cr > 1.288 was found to have 87.5% sensitivity and 83.3% specificity for OAB diagnosis. Conclusion: In conclusion, urine NGF/Cr and BDNF/Cr ratios may be useful markers for diagnosis of OAB. The BDNF/Cr ratio was found to be more significant in monitoring treatment response.